1995
DOI: 10.1063/1.113888
|View full text |Cite
|
Sign up to set email alerts
|

Pd induced lateral crystallization of amorphous Si thin films

Abstract: A thin palladium layer (∼40 Å) was selectively formed on top of amorphous silicon films before annealing and the effects of palladium layer on the crystallization behavior of the amorphous silicon films were investigated. It was observed that the amorphous silicon right under the Pd layer could be crystallized to grain sizes of several hundred angstroms by annealing at 500 °C. In addition, the area between the Pd thin pads, patterned by lithography, was found to be crystallized to grain sizes of a few tens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
72
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(78 citation statements)
references
References 0 publications
1
72
0
1
Order By: Relevance
“…Pd is a fast interstitial diffuser and almost insoluble in crystalline Si. The solubility of fast diffusing species in amorphous Si is known to be higher than that in crystalline Si and very sensitive to the defect concentration [51]. Pd does not dissolve Ge, and the solubility of Pd in Ge has not been studied [52].…”
Section: Palladium Propertiesmentioning
confidence: 99%
“…Pd is a fast interstitial diffuser and almost insoluble in crystalline Si. The solubility of fast diffusing species in amorphous Si is known to be higher than that in crystalline Si and very sensitive to the defect concentration [51]. Pd does not dissolve Ge, and the solubility of Pd in Ge has not been studied [52].…”
Section: Palladium Propertiesmentioning
confidence: 99%
“…In particular, the LTPS technology has been advanced, based on various crystallization techniques: e.g., sold phase crystallization, excimer laser annealing, rapid thermal annealing, metalinduced crystallization, etc,. [6][7][8][9][10][11][12][13][14] The crystallization techniques can be adapted for activation of ion-doped Si thin films, by making the possibility through slight modifications in processing variables. Ion-doping process accompanies the activation of ions implanted into polycrystalline Si (p-Si) as n-type or p-type.…”
Section: -5)mentioning
confidence: 99%
“…Having observed that in MILC by Pd, the rate changed inversely with the separation between the Pd pads, Lee et al [6] proposed that the MILC rate depended on the local Pd concentration. We have recently observed that in MILC by Ni [10], the rate decreased upon extended heat treatment.…”
mentioning
confidence: 99%
“…Recently, palladium (Pd) or nickel (Ni) [6], [7] was found to induce crystallization of -Si outside its coverage area. This phenomenon of metal induced "lateral" crystallization, or MILC for short, has been found to produce polycrystalline silicon thin films largely free of metal contamination, with better crystallinity than those produced by SPC, and resulting in better performing thin film transistors [8], [9].…”
mentioning
confidence: 99%